Fox-hunting in the 20th century British culture - Kořínková, Martina (Univerzita Pardubice, 2008)
The paper focuses on the character and position of fox hunting especially at the beginning of the 20th century in Great Britain. The main features, such as the participating social class, the etiquette and the whole atmosphere of the hunt, its rules and customs, and finally, the roles of participants and animals in the hunts, are analyzed. The findings are presented on the novel Memoirs of a Fox-hunting Man by Siegfried Sassoon. The work also focuses on the change of the position of traditional fox hunting in the British society at the turn of the millennium.
Honební jízdy na lišku v britské kultuře dvacátého století
Keywords: fox-hunting; Great Britain; upper-class; 20th century; traditions; honební jízdy na lišku; Velká Británie; vyšší společenská vrstva; 20. století; tradice